Desempenho de escolares bons leitores, com dislexia e com transtorno do déficit de atenção e hiperatividade em nomeação automática rápida - Capellini, Simone Aparecida [UNESP]; Ferreira, Tais De Lima; Salgado, Cíntia Alves; Ciasca, Sylvia Maria (Sociedade Brasileira de Fonoaudiologia, 2007)
PURPOSE: To characterize the performance of students with attention deficit hyperactivity disorder and dyslexia in rapid automatized naming and to compare it to the performance of children whose reading ability is considered to be in accordance to age and schooling. METHODS: A number of 30 students aged 8 to 12 years old attending 2nd to 4th grades in a public school participated in this study, divided into three groups, one formed by students with attention deficit and hyperactivity disorder, another one formed by students with dyslexia, and the other formed by students with good academic performance. RESULTS: The results revealed statistically significant differences, evidencing superior performance of the control group when compared to both the group of students with attention deficit and hyperactivity and the group with dyslexia in the subtests of colors, digit span, letters and objects. The results also revealed superior performance of the group of students with attention deficit compared to the group with dyslexia in rapid automatized naming. CONCLUSION: Good readers showed better performance when compared to both students with attention deficit and hyperactivity disorder and dyslexia, showing that this ability can be a prerequisite to reading development.

OBJETIVOS: Caracterizar o desempenho de escolares com transtorno do déficit de atenção e hiperatividade e com dislexia em nomeação automática rápida e comparar o desempenho destes escolares com aqueles que lêem conforme o esperado para idade e escolaridade. MÉTODOS: Participaram deste estudo 30 escolares na faixa etária de oito a 12 anos de idade de 2ª a 4ª séries do ensino público fundamental, divididos em três grupos de 10 escolares, sendo um grupo de escolares com transtorno do déficit de atenção e hiperatividade, um grupo de escolares com dislexia e um grupo de escolares com bom desempenho escolar. RESULTADOS: Os resultados revelaram diferenças estatisticamente significantes, evidenciando desempenho superior do grupo controle em relação ao grupo de escolares com transtorno do déficit de atenção e hiperatividade e ao grupo de escolares com dislexia nos subtestes de cores, dígitos, letras e objetos; e desempenho superior dos escolares do grupo com transtorno do déficit de atenção em relação ao grupo de escolares com dislexia em nomeação automática rápida. CONCLUSÃO: O presente estudo demonstrou que os escolares que lêem conforme o esperado para idade e escolaridade apresentaram melhor desempenho em relação ao grupo de escolares com transtorno do déficit de atenção e hiperatividade e o grupo com dislexia, demonstrando que tal habilidade pode ser considerada um pré-requisito para o desempenho em leitura.
Performance of good readers, students with dyslexia and attention deficit hyperactivity disorder in rapid automatized naming
Keywords: Attention deficit disorder with hyperactivity; Dyslexia; Underachievement; Reading; Transtorno da falta de atenção com hiperatividade; Dislexia; Baixo rendimento escolar; Leitura